Intraoperative Magnetic Resonance Imaging of Cerebral Oxygen Metabolism During Resection of Brain Lesions - Stadlbauer, Andreas; Merkel, Andreas; Zimmermann, Max; Sommer, Björn; Buchfelder, Michael; Meyer-Bäse, Anke; Rössler, Karl (World Neurosurgery, 2017)
OBJECTIVE: Tissue oxygen tension is an important parameter for brain tissue viability and its noninvasive intraoperative monitoring in the whole brain is of highly clinical relevance. The purpose of this study was the introduction of a multiparametric quantitative blood oxygenation dependent magnetic resonance imaging (MRI) approach for intraoperative examination of oxygen metabolism during the resection of brain lesions. METHODS: Sixteen patients suffering from brain lesions were examined intraoperatively twice (before craniotomy and after gross-total resection) via the quantitative blood oxygenation dependent technique and a 1.5-Tesla MRI scanner, which is installed in an operating room. The MRI protocol included T2*- and T2 mapping and dynamic susceptibility weighted perfusion. Data analysis was performed with a custom-made, in-house MatLab software for calculation of maps of oxygen extraction fraction (OEF) and cerebral metabolic rate of oxygen (CMRO2) as well as of cerebral blood volume and cerebral blood flow. RESULTS: Perilesional edema showed a significant increase in both perfusion (cerebral blood volume +21%, cerebral blood flow +13%) and oxygen metabolism (OEF +32%, CMRO2 +16%) after resection of the lesions. In perilesional nonedematous tissue only, however, oxygen metabolism (OEF +19%, CMRO2 +11%) was significantly increased, but not perfusion. No changes were found in normal brain. Fortunately, no neurovascular adverse events were observed. CONCLUSIONS: This approach for intraoperative examination of oxygen metabolism in the whole brain is a new application of intraoperative MRI additionally to resection control (residual tumor detection) and updating of neuronavigation (brain shift detection). It may help to detect neurovascular adverse events early during surgery.
EVALuna2:102201